Disciplining the conduct of young people in compulsory education policy and practice. Issue 1 (2nd January 2018) - Hodgson, David
ABSTRACT: Disciplining and pastoral power are central to the strategies and practices of intervening in the lives of young people deemed at risk of disengaging from school, or not completing their compulsory education. As an expression of power concerned with young people's welfare and self-improvement, disciplining and pastoral practices push young people towards greater responsibilism and employability. From 2004 to 2008, the State Government of Western Australia embarked on legislative change and policy implementation to increase the minimum compulsory school leaving age from 15 to 17. This facilitated a programme of interventions with some groups of young people deemed at risk of not meeting the newly minted minimum education requirements. Drawing on governmentality theory, research into this policy identifies and problematises its disciplining and pastoral practices. Interview data and policy documents are analysed to reveal the way that practices with young people, although framed as empowering and benign, worked to further connect them with the imperatives of neoliberalism.